A Calculation Method for Ground Shock Effect Induced by Hypervelocity Impact. (11th July 2022) - Zhang, Junnan; Wang, Derong; Xu, Tianhan; Li, Jie; Wang, Zhen; Ji, Yuguo; Xu, Xiaohui
Abstract : In the hypervelocity impact event, the strong ground shock effect is induced and may cause damage to underground engineering. The existing experimental methods and calculation procedures have difficulties in estimating the ground shock under complicated and large-scale impacts. Analytical and experiential methods independently prove that the shock energy radiating from a certain region underground is proportional to the mass of the materials in the region. Based on this relationship, an equivalent method is proposed to estimate the impact-induced ground shock with the help of abundant research results for underground explosions: The ground shock of two events can be seen as being equivalent as long as their crater sizes are the same. The calculated ground shock effect is compared with the measured values in impact experiments, and the results show great agreement.